Bridging the knowledge gap: from microbiome composition to function. Issue 3 (11th March 2015) - Faith, Jeremiah J
Abstract : Despite the wealth of metagenomic sequencing data, the functions of most bacterial genes from the mammalian microbiota have remained poorly understood. In their recent study (Yaung et al 2015), Wang, Gerber, and colleagues present a platform which allows functional mining of bacterial genomes for genes that contribute to fitness in vivo and holds great potential for forward engineering microbes with enhanced colonization abilities in the microbiota. Abstract : A functional metagenomics platform presented by Wang, Gerber, and colleagues (Yaung et al 2015) allows mining of bacterial genomes for genes that contribute to fitness in vivo and holds great potential for forward engineering microbes with enhanced colonization abilities in the microbiota.